(untitled) (Al-Academy, 2023)
The current research aims to: (know the effectiveness of the harvesting strategy in the achievement of the students of the Institute of Fine Arts in environmental art.- In order to know this effectiveness, the researcher put a main zero hypothesis and derived six sub-hypotheses from it. the usual way; As the research community reached (120) male and female students of the Fine Arts Institutes for the morning study in Baghdad. As for the research sample, it was chosen by the simple random method, and the number was (75) male and female students for the year 2021-2022 AD. The researcher applied a pre-knowledge test for the four groups of research to find out the level of previous experiences of students in the subject of environmental art. Teaching material vocabulary and objectives. After obtaining the validity and reliability of the test, the test was applied post-test on the four groups to see the effectiveness of the study plans according to the harvesting strategy.Among the statistical methods used by the researcher: Kruskal-Wiles test for equivalence in precognitive achievement. Holsty equation to ensure the validity of the cognitive achievement test. Kauder Richardson (20) test for reliability of cognitive test. The discriminatory power equation to find the percentage of the number of respondents who answered correctly in the paragraph. Mann Whitney test to find differences between the two groups according to the sub-hypotheses.- The results of the research showed that the students of the two experimental groups who studied environmental art according to the harvesting strategy excelled over the students of the two control groups who studied in the traditional way.- The results also showed that there were statistically significant differences between the ranks of the students of both groups, the experimental males and the experimental females, and that the direction of this difference was in favor of the females of the experimental group who studied according to the harvest strategy.Based on the results, the researcher concluded:1. The harvesting strategy worked on transferring students from a state of direct reception of information to searching for it, and this is the opposite of the usual method.2. The steps of the harvest strategy enabled the students to make qualitative changes in their thinking pattern, which helped them to distinguish the correct solutions and choose them from among many solutions.The researcher recommends: presenting the educational material to the students in the form of problems that affect the life of the learner, and this encourages thinking and finding appropriate solutions to them.